68 LEFT ATRIAL APPENDAGE OCCLUSION AFTER THROMBOEMBOLIC EVENTS OR LEFT ATRIAL APPENDAGE SLUDGE DURING ANTICOAGULATION THERAPY: TWO IS BETTER THAN ONE. REAL-WORLD EXPERIENCE FROM A TERIARY CARE CENTER. (15th December 2022) - Margonato, Davide; Preda, Alberto; Ingallina, Giacomo; Rizza, Vincenzo; Fierro, Nicolai; Ancona, Francesco; Agricola, Eustachio; Della Bella, Paolo; Mazzone, Patrizio
Abstract: Background: Although, in recent years, the indications for left atrial appendage occlusion (LAAO) have expanded, its role for patients that during oral anticoagulant (OAC) therapy suffer from ischemic events or present LAA sludge is still to be defined. Moreover, data on the best anticoagulant regiment post-LAAO for these patients is scarce. Purpose: Aim of this study was to present our experience with a hybrid approach consisting of LAAO+ lifelong OAC therapy in this cohort of high-ischemic risk patients. Methods: At our center, from January 2013 to June 2022, 102 patients underwent percutaneous LAAO because, despite optimal OAC, suffered from ischemic events or were found to have LAA sludge. In the absence of a high bleeding risk, patients were then discharged with the aim of maintaining lifelong OAC. Moreover, to confirm the feasibility and the long-term efficacy of LAAO in this cohort, the group was matched 1:1 to a patient population who underwent LAAO in our center to prevent ischemic events and without sludge at preprocedural TEE. The primary endpoint was the composite of all-cause death (ACD) and major adverse cardiovascular events (MACE) consisting of ischemic stroke, systemic embolism (SE) and major bleeding Results: Procedural success was achieved in 98% of patients. 70% of patients were discharged with anticoagulant therapy, while 30% only with antiplatelet therapy. After a median follow-up of 47.2 months, none of the patients discharged with OAC had stroke, SE or device-related thrombosis. The primary composite endpoint of ACD+ MACE occurred in 27 patients (26%). Patients affected by the primary outcome had more history of coronary artery disease (CAD, p<0.001), diabetes mellitus (DM p=0.003), left ventricular systolic dysfunction (LVSD, p=0.004) and were more often discharged without OAC (p=0.005) compared to those who weren't. After univariate and multivariate analyses, CAD (OR 5.1, CI 1.89- 14.27, p=0.003) and OAC at discharge (OR 0.29, CI 0.11- 0.80, p=0.017) were independently associated with the primary endpoint. At survival analyses, there was a constant trend toward a longer survival free from the primary composite endpoint for patients discharged in anticoagulant therapy compared to those without, but not reaching statistical significance (p=0.41). Finally, after propensity score matching, Kaplan Meyer curves showed that there was no significant difference in the long-term survival free from the primary composite EP according to the indication for LAAO (p=0.19). Conclusions: We report our experience on the management of patients with ischemic events or LAA sludge despite OAC. Percutaneous LAAO was feasible with a high procedural success. Our hybrid therapeutical approach consisting of LAAO+ lifelong OAC, if feasible in the absence of high bleeding risk, was safety and effective in reducing clinical ischemic events after a long-term follow-up.